Relações de gênero na educação infantil: tensões contemporâneas e expressões de resistência de docentes da rede pública municipal de educação de Belo Horizonte - Cláudia Silva Ribeiro Cruz (2021)
The purpose of this dissertation was to analyze the discourse of pre-school education teachers about gender relations in childhood, seeking to apprehend training, personal trajectory, and pedagogical practices of teachers from the municipal education network in Belo Horizonte that work with the theme. For this, we seek to raise, on one hand, the training processes of the municipal network, through the production of documents and conducting training courses. On the other hand, to know the processes of teacher training, from childhood to the initial and continued professional training. Finally, raising the daily pedagogical practice in early childhood education, as well as analyzing what contemporary tensions mean in dealing with the theme. The methodology involved documentary analysis, open semi-structured interviews with 11 educators who acted as trainers or students from continuing education courses at the institution. The importance of life trajectory and training spaces in the deconstruction of a heteronormative view of gender relations was observed, in addition to the impact of the silencing of this theme by political-religious groups and the construction of resistance actions by the teachers in their professional practices.